2009
DOI: 10.1111/j.1752-4571.2009.00095.x
|View full text |Cite
|
Sign up to set email alerts
|

ORIGINAL ARTICLE: Mitigating fisheries‐induced evolution in lacustrine brook charr (Salvelinus fontinalis) in southern Quebec, Canada

Abstract: Size-selective mortality caused by fishing can impose strong selection on harvested fish populations, causing evolution in important life-history traits. Understanding and predicting harvest-induced evolutionary change can help maintain sustainable fisheries. We investigate the evolutionary sustainability of alternative management regimes for lacustrine brook charr (Salvelinus fontinalis) fisheries in southern Canada and aim to optimize these regimes with respect to the competing objectives of maximizing mean … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
29
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 26 publications
(31 citation statements)
references
References 75 publications
(185 reference statements)
2
29
0
Order By: Relevance
“…Analyses of long-term datasets have supported the understanding that FIE in maturation schedules, reproductive investments, and growth rates can occur in exploited populations within a few decades (Olsen et al 2004;Jørgensen et al 2007;Kuparinen and Merilä 2007). Models of evolutionary dynamics under different fishing regimes have corroborated this finding (Thériault et al 2008;Dunlop et al 2009;Enberg et al 2009;Okamoto et al 2009;Eikeset et al 2013). …”
Section: Introductionmentioning
confidence: 52%
“…Analyses of long-term datasets have supported the understanding that FIE in maturation schedules, reproductive investments, and growth rates can occur in exploited populations within a few decades (Olsen et al 2004;Jørgensen et al 2007;Kuparinen and Merilä 2007). Models of evolutionary dynamics under different fishing regimes have corroborated this finding (Thériault et al 2008;Dunlop et al 2009;Enberg et al 2009;Okamoto et al 2009;Eikeset et al 2013). …”
Section: Introductionmentioning
confidence: 52%
“…With the number of empirical studies indicative of harvestinduced evolution in maturation schedules of commercially exploited marine fish stocks mounting rapidly (e.g., Grift et al, 2003Grift et al, , 2007Olsen et al, 2004Olsen et al, , 2005Barot et al, 2005;Baulier et al, 2006;Mollet et al, 2007;Okamoto et al, 2009), it is becoming increasingly important to interpret observed trends in terms of sufficiently realistic eco-evolutionary models. Since, as a matter of principle, it will never be possible to prove fisheriesinduced evolution as the unequivocal cause of maturation trends , models are key to assessing whether the observed trends comply with those predicted by life-history theory: the closer the match, the more an interpretation of observed trends in terms of fisheries-induced evolution is strengthened.…”
Section: Discussionmentioning
confidence: 99%
“…Life-history theory predicts that increased mortality devalues life-history processes occurring later in life, relative to those occurring earlier (e.g., Law, 1979;Stearns, 1992;Ernande et al, 2004). Therefore, systematic reductions in age and size at maturation observed for stocks exposed to heavy fishing (e.g., Jørgensen, 1990;Rijnsdorp, 1993a;Trippel, 1995) are suggestive of fisheries-induced evolution (e.g., Grift et al, 2003Grift et al, , 2007Barot et al, 2004Barot et al, , 2005Olsen et al, 2004Olsen et al, , 2005Baulier et al, 2006;Dieckmann and Heino, 2007;Mollet et al, 2007;Heino andDieckmann, 2008a, 2008b;Thé riault et al, 2008;Arlinghaus et al, 2009;Okamoto et al, 2009). These concerns add to those raised more broadly about the negative impact of fisheries on the ecosystems in which all fish stocks are embedded (e.g., Jennings and Kaiser, 1998).…”
Section: Introductionmentioning
confidence: 92%
“…To date, there have only been a few attempts to quantify 8 yield changes resulting from fishing-induced evolution, and most of them predicted yield to 9 decline (Law and Grey 1989; Heino 1998; Andersen and Brander 2009; Okamoto et al 2009). 10 Also experiments have demonstrated declining yields in response to size-selective exploita-11 tion (Conover and Munch 2002).…”
mentioning
confidence: 99%